Two Types of Endosymbiotic Bacteria in the Enigmatic Marine Worm Xenoturbella bocki - Kjeldsen, Kasper Urup (American Society for Microbiology (ASM), 2010)
Two types of endosymbiotic bacteria were identified in the gastrodermis of the marine invertebrate Xenoturbella bocki (Xenoturbellida, Bilateria). While previously described Chlamydia-like endosymbionts were rare, Gammaproteobacteria distantly related to other endosymbionts and pathogens were abundant. The endosymbionts should be considered when interpreting the poorly understood ecology and evolution of Xenoturbella.